Inflammatory Myofibroblastic Tumors in the Uterus: Childhood-Case Report and Review of the Literature - Etlinger, Péter; Kuthi, Levente; Kovács, Tamás (Frontiers in Pediatrics, 2020)
Inflammatory myofibroblastic tumor (IMT) is a spindle cell neoplasm with low malignant potential, which may appear in different parts of the body. Uterine localization is rare, especially among children. Etiology is unclear, although some authors suggest underlying trauma or distress. A 3.5-year-old girl was treated at our institute for recurring vaginal bleeding without injury or known pathology. Physical examination and laboratory analysis revealed no specific findings, contrast-enhanced MRI found a 25x28x30 mm-sized inhomogeneous soft tissue mass in the uterus wall, which was excised in toto. Histological examination identified a spindle cell pattern, and the FISH test revealed ALK gene rearrangement, the lesion was defined as an IMT. 6 cases were published to date, and their diagnostic methods are not equivocal, CT and PET CT were preferred instead of MRI. Aggressive therapy seems to be exaggerated according to low recurrence and metastasis occurrence, and crizotinib is proved as good therapeutic agent in those cases. Biopsy and histology has important role in order to distinguish IMT from malignancies completed with FISH examination because ALK positivity strengthens the diagnosis. No lethal outcome was published among children, as our patient is also symptom-free after 3 years.